Mobile Telecommunications and Social Development in Bangladesh - Talukdar, Kamrul Huda; Sayeed, Shahran Abu (International Journal of Social and Administrative Sciences, 2020)
Social development is the transformation of institutions to empower people. Since there is no comprehensive theory guiding on how this is achievable, World Bank, based on their experience, identified three operational principles to guide its approach to social development: inclusion, cohesion, and accountability. Social Inclusion encourages equal opportunities for men and women to contribute to society. Cohesive society allows individuals to work together to achieve common goals peacefully by overcoming hurdles. Accountable institutions ensure transparency and respond to public interests effectively and equitably. This paper employs an exploratory study and aims to address how Grameenphone Limited, a leading multinational telecommunication company in Bangladesh is contributing to the country’s social development. To investigate the research questions a documentary research approach is pursued. Documentary research is the use of documentary sources in social research. It refers to the analysis of the documents that contains information about the phenomenon under investigation. The findings show that Grameenphone Ltd. played a crucial role in creating equal opportunities for men and women to contribute to society. Furthermore, it also contributed in creating a cohesive society which allowed individuals to work together to achieve common goals peacefully by overcoming hurdles. Lastly, though social compliance, CSR and environmental sustainability, GP ensured transparency and responded to public interests effectively and equitably. To the best of our knowledge, this is one of the first studies which strive to explore how mobile telecommunications can contribute to social development.